Lynch Syndrome-Associated Endometrial Cancer With Combined EPCAM-MSH2 Deletion: A Case Report - Huang, Rong; Deng, Xiangyu; Zhang, Zhenhua; Wen, Qinglian; Li, Dan (Frontiers in Oncology, 2022)
Background Lynch syndrome (LS), an autosomal dominant disorder, is characterized by germline pathogenic variants in DNA mismatch repair (MMR) genes like MSH2. EPCAM deletions cause a minority (3%) of LS cases. However, there are only a few reports of LS-associated endometrial cancer (LS-EC) induced by the inactivation of the MSH2 gene due to EPCAM deletions. Case Presentation We present the case of a 45-years old woman diagnosed with endometrial cancer (EC). Definitive surgery revealed meso-differentiated endometrioid adenocarcinoma, stage IA without lymph-vascular space invasion. Four months later, she received radiation therapy (125I radioactive seeds implantation), and platinum-containing regimen combined chemotherapy because of vaginal stump metastasis of EC. After five years, we performed immunohistochemistry (IHC) on pelvic mass because of presacral metastatic lymph node. IHC showed the absence of MSH2 and MSH6 protein expression in the pelvic mass tissue. Peripheral blood was used for genetic testing based on her cancer diagnosis and family history of cancer in close relatives. Genetic testing revealed deletions of exon 8 and 9 in EPCAM and deletions of exon 1 and 8 in MSH2; thus, we diagnosed the presence of LS. The patient underwent interstitial brachytherapy (BT) of the presacral metastatic lymph node. Conclusion This case highlights that patients with LS-EC who are carriers of combined EPCAM-MSH2 deletion might experience better oncologic outcomes even with early recurrence.